2017
DOI: 10.1038/s41467-017-01194-z
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history and biologically relevant genetic variation of Native Mexicans inferred from whole-genome sequencing

Abstract: Understanding the genetic structure of Native American populations is important to clarify their diversity, demographic history, and to identify genetic factors relevant for biomedical traits. Here, we show a demographic history reconstruction from 12 Native American whole genomes belonging to six distinct ethnic groups representing the three main described genetic clusters of Mexico (Northern, Southern, and Maya). Effective population size estimates of all Native American groups remained below 2,000 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 65 publications
(77 reference statements)
9
40
0
Order By: Relevance
“…Ruben Lisker performed the first works of Mexican genetics in indigenous populations in the 1960s [ 9 , 22 ], in which he tried to know the degree of admixture as well as the main ancestral components present in these populations. Recently, some studies have been carried out at the molecular level with the aim of knowing the underlying relationships between indigenous and mestizos [ 19 21 ], to reconstruct the history of the Amerindian populations in the continent [ 50 ] and their development throughout the country [ 21 ]. Additionally, these works have explored the possible effects of the genetic content in the clinic context [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruben Lisker performed the first works of Mexican genetics in indigenous populations in the 1960s [ 9 , 22 ], in which he tried to know the degree of admixture as well as the main ancestral components present in these populations. Recently, some studies have been carried out at the molecular level with the aim of knowing the underlying relationships between indigenous and mestizos [ 19 21 ], to reconstruct the history of the Amerindian populations in the continent [ 50 ] and their development throughout the country [ 21 ]. Additionally, these works have explored the possible effects of the genetic content in the clinic context [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few works about population genetics in Mexico [ 19 21 ]. The first studies were performed by Lisker and colleagues, in indigenous and mestizo populations by studying several blood antigens [ 9 , 22 ]; however, few populations were studied and currently there is lack of information about blood groups distribution in the country, whereby it is essential to get this information to help health institutions for the effective management of their blood banks that facilitate transplant medicine practices.…”
Section: Introductionmentioning
confidence: 99%
“…(ran on 28/06/17) To test for enrichment in GO categories among genes with novel missense SNV we used WebGestalt online tool(J. Wang et al 2013) as reported in (Romero-Hidalgo et al 2017a).…”
Section: Formentioning
confidence: 99%
“…A second limitation is enrollment of Mexican population from the same city, not having a random sample from overall Mexican population. However, considering the ethnical background of Mexicans in general, it is not expected to have a great variation of phenotypes since the habitants ancestry is fairly homogeneous [27]. Thirdly, due to ethical reasons, the trials included in this study were executed following a single dose/concentration schedule, in order to reduce the unnecessary risk of possible harm, especially since the active ingredients are known compounds and their posology has already been stablished.…”
Section: Discussionmentioning
confidence: 99%